Pengaruh Aktivitas Tunneling, Opini Audit Dan Ukuran Dewan Komisaris Terhadap Kinerja Perusahaan Dengan Metode Altman Z-Score - Rafika Misdiyanti; Dudi Pratomo; Djuznimar Zultilisna (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This study uses the Altman z-score method to examine the effects of company size, profitability, and leverage as control variables on company performance in the primary consumer goods sector companies listed on the Indonesia Stock Exchange between 2017 and 2021. There are 52 companies in total in this population. Purposive sampling was the sampling approach employed in order to collect data from 260 observations. Secondary data are used in this research's quantitative methodology. Panel data regression analysis using Eviews 12 is the technique employed. The study's findings indicate that corporate performance is simultaneously influenced by tunnelling activity, audit opinion, and board size, with firm size, profitability, and leverage as control factors. Partially, audit findings and tunnelling activities have no impact on a company's performance. The size of the board of commissioners, nevertheless, has a detrimental impact on the operation of the business.